The Effect of an Acidic Food-Simulating Environment on the Shear Bond Strength of Self-Ligating Brackets with Different Base Designs - Ahmad Sheibaninia; Sepehr Sepasi; Mohammad Ali Saghiri; Setareh Sepasi (Hindawi Limited, 2014)
Aim. This study aims to evaluate the effect of acidic food simulant and (acetic acid 3%) on the shear bond strength (SBS) and adhesive remnant index (ARI) scores of one conventional and three different self-ligating brackets with different base designs. Materials and Methods. Freshly extracted first maxillary premolars (n=160) were embedded in resin blocks. A conventional stainless steel bracket, Equilibrium 2, and three types of self-ligating brackets, Speed, In-Ovation R, and Damon 3MX, were bonded to teeth and exposed to distilled water (groups 1, 3, 5, and 7) or acetic acid 3% (groups 2, 4, 6, 8) for 12 weeks. SBS and ARI were calculated and statistical analysis was performed with the analysis of variance (SBS) or χ2 test (ARI) to compare values between the different groups. Results. Equilibrium 2 and In-Ovation R showed a significantly lower SBS in the acidic environment than in distilled water. Significant differences in ARI scores were found for Equilibrium 2 after immersion in an acidic environment, shifting from 0 in distilled water to 2 in an acidic environment. Conclusions. Equilibrium 2 and In-Ovation R brackets showed a significant decrease in SBS after a 12-week immersion in acetic acid 3%, although all groups showed clinically acceptable SBS. Equilibrium 2 showed significant differences in ARI scores when exposed to acetic acid 3%.